2015
DOI: 10.1093/schbul/sbv178
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Network Disturbances in the Psychosis Spectrum

Abstract: Weaker connections and decreased centrality of parietal hubs characterize the structural brain network in subjects with psychotic symptoms. These differences are more notable in clinical than in subclinical subjects with psychotic experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
5
27
1
Order By: Relevance
“…Otte et al (2015) showed that MST characteristics are sensitive to aging effects, which was replicated in the present work. A recent study in patients with psychotic symptoms showed that MST analysis is a viable method to directly compare structural brain networks of different populations, and to capture psychosis‐related alterations in brain network topology (van Dellen et al, 2015). MST analysis has also proven useful in several empirical studies on functional brain networks, showing a less integrated network in patients with neurological and psychiatric disorders including schizophrenia, epilepsy, Parkinson's disease, and multiple sclerosis (Stam, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otte et al (2015) showed that MST characteristics are sensitive to aging effects, which was replicated in the present work. A recent study in patients with psychotic symptoms showed that MST analysis is a viable method to directly compare structural brain networks of different populations, and to capture psychosis‐related alterations in brain network topology (van Dellen et al, 2015). MST analysis has also proven useful in several empirical studies on functional brain networks, showing a less integrated network in patients with neurological and psychiatric disorders including schizophrenia, epilepsy, Parkinson's disease, and multiple sclerosis (Stam, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the MST is a unique subset of connections provided that all connection weights are unique, which makes it possible to create an empirical reference network of the connections in a healthy human brain. Recent studies have shown that MST analysis can be used to capture network alterations due to aging and disease in both functional and structural imaging data (Boersma et al, 2010;Otte et al, 2015;van Dellen et al, 2014van Dellen et al, , 2015.…”
Section: ; Vanmentioning
confidence: 99%
“…Importantly, the IFN approach avoids another pitfall found in regression-based methods: reduced comparability between samples. Because the number of edges is kept constant and does not vary on the basis of sample size, network measures are less biased when attempting to compare between crosssectional or clinical and non-clinical samples (Tewarie et al, 2015;van Dellen et al, 2015). In the TMFG method, for example, the WSS-SF network, with 60 variables, will always have 174 edges (3n -6 edges).…”
Section: Information Filtering Networkmentioning
confidence: 99%
“…Psychotic symptoms are within the general population, 92,95,101,108,181,204,205 on a continuum, 204,205 and risk factors for developing psychotic disorders. 95,101 Psychotic symptoms are also symptoms of psychopathological states such as psychosis and psychotic disorders, 98,105,[111][112][113]115,127,138,145,146,149,154,156,162,164,167,169,174,177,179,184,188,189,[191][192][193][196][197][198] dementia, 103,107,116,117,125,135,137,139,140,…”
Section: Common Terminologymentioning
confidence: 99%